Streptomycin Sulfate–Loaded Niosomes Enables Increased Antimicrobial and Anti-Biofilm Activities - Mansouri, Maryam; Khayam, Nazanin; Jamshidifar, Elham; Pourseif, Tara; Kianian, Sepideh; Mirzaie, Amir; Akbarzadeh, Iman; Ren, Qun (Frontiers in Bioengineering and Biotechnology, 2021)
One of the antibiotics used to treat infections is streptomycin sulfate that inhibits both Gram-negative and positive bacteria. Nanoparticles are suitable carriers for the direct delivery and release of drug agents onto infected locations. Niosomes are one of the new drug de-livery systems that have received much attention today due to their excellent biofilm pene-tration property and controlled release. In this study, niosomes containing streptomycin sulfate were prepared by thin layer hydration method and optimized based on size, polydisper-sity index (PDI), and encapsulation efficiency (EE%) characteristics. It was found that Span 60 to Tween 60 ratio of 1.5 and surfactant to cholesterol ratio of 1.015 led to an optimum formulation with a minimum of size, low PDI, and maximum of EE at 97.8 nm, 0.27, and 86.7%, respectively. The drug release investigation showed that 50.0±1.2% of streptomycin sulfate was released from the niosome in 24 hours and reached 66.4±1.3% by the end of 72 h. Stability studies within 2 months at 25 ºC and 4 ºC showed more acceptable stability of samples kept at 4 ºC. Consequently, antimicrobial and anti-biofilm activities of streptomycin sulfate-loaded niosomes against Staphylococcus aureus, Escherichia coli and Pseudomonas aeruginosa were found significantly higher than free drug, the minimum inhibitory concentration values decreased 4-8 fold. Furthermore, niosomes encapsulated streptomycin up to 1300 µg/mL exhibited negligible cytotoxicity against the human foreskin fibroblasts cell line, whereas the free drug exhibited slight cytotoxicity at this concentration. Desired physical characteristics and low toxicity of niosomal nano-carriers containing streptomycin sulfate made them a demanded candidate for the treatment of current bacterial infections and biofilms.